Oogenesis 2012
DOI: 10.1007/978-0-85729-826-3_2
|View full text |Cite
|
Sign up to set email alerts
|

Origin, Migration, and Proliferation of Human Primordial Germ Cells

Abstract: The fi rst histological observations about the origin of the precursors of gametes termed primordial germ cells (PGCs) in extragonadal regions and their subsequent migration into the developing gonads in human embryos date back to the early twentieth century. Fuss (Anat Am 39:407-409, 1911, Anat EntwMech 81:1-23, 1912 and Felix (Die Entwicklung der Harn-und Geschlechtsorgane. In: Keibel-Mall Handbuch der 1qEntwick-lungageschichte des Menshen, vol 2. Leipzig, Hirzel, pp 732-955, 1911) were apparently the fi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 132 publications
5
76
0
2
Order By: Relevance
“…BMP2, BMP4, and WNT3A are expressed at posterior epiblast around the area of PGC specification. The place where human PGCs were identified in the earliest developmental stage of embryos is on the endoderm wall of yolk sac at the angle with allantois around the end of the third week of gestation (7). This is the same place as migrating mouse PGCs are observed.…”
mentioning
confidence: 81%
“…BMP2, BMP4, and WNT3A are expressed at posterior epiblast around the area of PGC specification. The place where human PGCs were identified in the earliest developmental stage of embryos is on the endoderm wall of yolk sac at the angle with allantois around the end of the third week of gestation (7). This is the same place as migrating mouse PGCs are observed.…”
mentioning
confidence: 81%
“…Human PGCs have been also identified by APase staining at around 4 th week of gestation in the wall of the yolk sac and hindgut and move to the GRs by 7 th week (for a review, see [7]) Recent studies have shown similar gene expression patterns in mouse 11.5 dpc and human 7 th -9 th week PGCs. In particular, germline (BLIMP1, AP2γ, UTF1, DAZL, Kit and DDX4) and pluripotency genes (OCT4, NANOG, PRDM14 and LIN28) (Fig.…”
Section: Pgc Formation and Migrationmentioning
confidence: 92%
“…Human PGCs proliferate during migration and after GR colonization and a subset of oogonia and gonocytes continues proliferation up to the second trimester of gestation (for a review, see [7]). Several growth factors and cytokines have been reported to affect positively or negatively, the proliferation/survival of mouse PGCs in vitro and/or in vivo.…”
Section: Pgc Survival/proliferationmentioning
confidence: 99%
“…These data suggest that the ExE is essential for proper PGC specification and development in the mouse. However, since the anatomy and morphology of the mouse and the primate embryo are fundamentally different, with a flat germ disc in primates and an egg cylinder in the mouse [4,33] , there is no direct structural counterpart of the mouse ExE in the primate embryo [34] . Recently, it was shown that the nascent (pregastrulation) amnion is the origin of PGCs in the cynomolgus monkey [13] .…”
Section: The Role Of the Amnion And The Extraembryonic Ectodermmentioning
confidence: 99%